If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 = 5 + 2d Solving 9 = 5 + 2d Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '-2d' to each side of the equation. 9 + -2d = 5 + 2d + -2d Combine like terms: 2d + -2d = 0 9 + -2d = 5 + 0 9 + -2d = 5 Add '-9' to each side of the equation. 9 + -9 + -2d = 5 + -9 Combine like terms: 9 + -9 = 0 0 + -2d = 5 + -9 -2d = 5 + -9 Combine like terms: 5 + -9 = -4 -2d = -4 Divide each side by '-2'. d = 2 Simplifying d = 2
| 4t=153t | | 4m-2=2m | | 4x-25+2x+5=x | | -.4d=-6.4 | | 1.7p-3=0.9+13 | | 3b-4b=4 | | 7-4=6x+11 | | 8+4x=5x+5 | | -3y-19+5y=-22 | | 4x-6x-16=-2x+3-16 | | 7x+2=5x+15 | | .25x-8+.5x=19 | | 10-2x=3(x+4)-2 | | 10h=-.1 | | 9=2j+1 | | 9=1+2b | | 3x+2(x+2)=5x+4 | | -2.5s=25 | | 2x+2+7x=-6x-2x | | .4x-8+.5x=19 | | 2(x+1)=3(x+4) | | 4+2i=4 | | 12y=1x+b | | -8g=.48 | | 0.6r=.0005 | | -7y=-6.3 | | 2(x+1)=3(x+4)+10 | | 0.6=r+.0005 | | (3x^2-2x^2+2x-5)*x+1= | | x+(-28)=53 | | .3k=-12 | | 14=6-4y |